Design and research of intelligent motion intervention system for infectious diseases - Lina Xie (Elsevier, 2020)
In order to provide a more valuable means of examination, treatment and rehabilitation for patients with chronic diseases by using the intelligent motion control training system, simple obesity, diabetes mellitus, heart disease, hypertension and other four types of chronic diseases with the highest incidence of diseases are taken as the research object. Several patients with each disease are randomly divided into two or three groups to explore the importance of intelligent motor intervention system for patients with chronic diseases during examination, treatment and rehabilitation. The results show that the disease indicators of chronic diseases participated in by intelligent exercise intervention system are improved and decreased in different research diseases. In addition, the intelligent motion intervention system has realized the whole function through four stages: requirement analysis, function design, system implementation and system testing. Finally, it is verified that its function and performance can meet people's needs and achieve the desired goals. At the same time, it provides useful reference for standardizing drug use behavior, improving drug efficacy, reducing adverse reactions, and improving the level of clinical treatment. Thus, under the intervention of intelligent motor system based on K-proximity algorithm, rehabilitation treatment of chronic diseases can not only reduce the physical and mental discomfort of patients, quickly restore their health, but also reduce the pain of patients, reduce anxiety, improve patient satisfaction, shorten the diagnosis and treatment time and reduce the cost of examination, which has obvious improvement effect. Therefore, this study is of great significance for providing a more valuable means of examination, treatment and rehabilitation for patients with chronic diseases.